Analysis of the fine specificity of rat, mouse and human TAP peptide transporters - Neefjes, Jacques; Gottfried, Eva; Roelse, Joost; Grommé, Monique; Obst, Reinhard; Hämmerling, Günter J.; Momburg, Frank (European journal of immunology, 1995)
Prior to their association with major histocompatibility complex (MHC) class I molecules, peptides generated from cytosolic antigens need to be translocated by the MHC-encoded peptide transporter (TAP) into the lumen of the endoplasmic reticulum (ER). While class I molecules possess well-known binding characteristics for peptides, the fine specificity of TAP for its peptide substrates has not been analyzed in detail. Previously, we have studied the effect of amino acid variations at the N-terminal, the C-terminal, and the penultimate residue on the efficiency of peptide translocation. Using permeabilized cells, we have shown that TAP pre-selects peptides in an allele- and species-specific manner, for which only the C-terminal residue is crucial. This finding is confirmed in the present study by using microsomes containing different TAP. The influence of amino acid substitutions at positions 2 to 7 of 9-residue model peptides on TAP-dependent peptide translocation is systematically examined. Only a few amino acid substitutions at these positions affect the efficiency of peptide translocation significantly, e.g. Pro at position 2 or 3 negatively influences transport whereas Glu at positions 6 and 7 enhances transport. The differences in translocation by the rat TAP alleles a or u, mouse TAP and human TAP are, however, minor for the peptide with internal substitutions used in this study. These results show that the C-terminal residue essentially governs the species-specific substrate specificity of TAP.
Gesehen am 24.07.2025